2005
DOI: 10.1128/jvi.79.2.1207-1214.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Loop of the Potato Leafroll Virus Coat Protein Is Involved in Virion Assembly, Systemic Movement, and Aphid Transmission

Abstract: Two acidic domains of the Potato leafroll virus (PLRV) coat protein, separated by 55 amino acids and predicted to be adjacent surface features on the virion, were the focus of a mutational analysis. Eleven site-directed mutants were generated from a cloned infectious cDNA of PLRV and delivered to plants by Agrobacterium-mediated mechanical inoculation. Alanine substitutions of any of the three amino acids of the sequence EWH (amino acids 170 to 172) or of D177 disrupted the ability of the coat protein to assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 31 publications
(44 reference statements)
6
101
1
1
Order By: Relevance
“…The results indicated that regardless of whether the RTD mutant incorporated RTP into the virion (RFI, EDE and SST) or not (QSS, GHPE, ERD and SYG), none of the RTD mutants were aphid transmissible (Table 2). Incorporated RTP, as well as surface loops of the CP, have been shown to be required for aphid transmission of poleroviruses (Brault et al, 2003;Bruyere et al, 1997;Jolly & Mayo, 1994;Kaplan et al, 2007;Lee et al, 2005). The results reported here showing that non-incorporating RTP mutants were not aphid transmissible are consistent with previous reports that RTP is required for aphid transmission.…”
Section: Aphid Transmission Of the Rtd Mutants Via Tissue Feeding Andsupporting
confidence: 83%
See 4 more Smart Citations
“…The results indicated that regardless of whether the RTD mutant incorporated RTP into the virion (RFI, EDE and SST) or not (QSS, GHPE, ERD and SYG), none of the RTD mutants were aphid transmissible (Table 2). Incorporated RTP, as well as surface loops of the CP, have been shown to be required for aphid transmission of poleroviruses (Brault et al, 2003;Bruyere et al, 1997;Jolly & Mayo, 1994;Kaplan et al, 2007;Lee et al, 2005). The results reported here showing that non-incorporating RTP mutants were not aphid transmissible are consistent with previous reports that RTP is required for aphid transmission.…”
Section: Aphid Transmission Of the Rtd Mutants Via Tissue Feeding Andsupporting
confidence: 83%
“…Using Agrobacterium tumefaciens cultures containing the fulllength cDNA of the PLRV WT or one of the mutant viruses, agroinfiltration into mesophyll cells and agroinjection into vascular cells were done as described previously by Lee et al (2005) and Kaplan et al (2007). Translation and accumulation of RTP was measured in agroinfiltrated tissue samples by Western blot analysis as described previously in Lee et al (2005) and Kaplan et al (2007). Nicotiana benthamiana, N. clevelandii, Physalis floridana and Solanum sarrachoides plants were agroinjected and analysed for systemic infection as described previously by Lee et al (2002) and Kaplan et al (2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations